The Effectiveness Of Giving Calendula Oil On Wound Healing In White Rats (Rattus Norvegicus) - Heny Noor Wijayanti; Yana Luthfiyati (Universitas Andalas, 2021)
Research Background : In the process of childbirth, there is often a tear in the birth canal, especially in the perineum, which is known as a ruptured perineum. Some herbal ingredients that are thought to be healing wounds are nyamplung seed oil/tamanu oil (Calophyllum inophyllum L.), red ginger oil (Zingiber officinale var rubrum) and marigold flower oil/calendula oil (Calendula officinalis). Calendula ointment has the benefit of healing episiotomy wounds faster than the use of povidone iodine.Research Objective: To determine the effectiveness of giving calendula oil herbal ingredients to wound healing in female white rats.Research Methods: Laboratory experimental research using a completely randomized design using the Post Test Only Control Group Design pattern. The population in this study were female white rats (Rattus norvegicus). The sample selection was used by simple random sampling. Univariate analysis of wound healing was performed to obtain the mean ± SD and bivariate analysis using one-way ANOVA using computer software.The results of the study: The results of statistical tests showed that the One way Anova test obtained p value = 0.000 with a value of = 0.05 (p < ) where the administration of Calendula Oil on white rat wounds was more effective than without treatment.Conclusion: Based on the results of the study, it can be concluded that giving calendula oil to female white rats is effective in healing wounds.